THE EFFECT OF TRANSFER PRICING, LEVERAGE, AND CAPITAL INTENSITY ON TAX AVOIDANCE - Andre Rizky Mandala Pamungkas Suherman; Murtanto (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This study aims to provide empirical evidence that transfer pricing, leverage, and capital intensity influence tax avoidance. The subjects of this research are energy mining companies listed on the Indonesia Stock Exchange from 2020 to 2023. Sample selection was conducted using purposive sampling, resulting in 17 companies that met the criteria. The data used consisted of secondary data from annual financial reports. Data were analyzed using multiple linear regression. The results of this study indicate that (1) Transfer Pricing does not affect tax avoidance; (2) Leverage affects tax avoidance; (3) Capital Intensity does not affect tax avoidance; (4) collectively, Transfer Pricing, Leverage, and Capital Intensity significantly influence Tax Avoidance.